Use of Question-And-Answer Method in Teaching English Prepositions to Primary School Learners - Nephawe, Farisani Thomas; Lambani , Matodzi Nancy (International Journal of Language and Literary Studies, 2022)
Primary school education in South Africa is based on the premise that foreign language learners study English as First Additional Language. Although the ideal situation for acquiring any language is to live among native speakers, most learners are not exposed to native English speakers. As the teaching methods employed are governed by this principle, the question-and-answer method provides immediate feedback to teachers and enhances learners’ proficiency in English prepositions. The paper investigated if the question-and-answer method improves learners' proficiency in the learning of English prepositions of movement. Using a qualitative approach, the researchers interviewed and observed the teaching of English prepositions of movement by English First Additional Language teachers. Three rural Grade Six Lwamondo Primary school teachers in Limpopo Province, South Africa were sampled depending on the use of traditional teaching methods. The paper established that the question-and-answer method improved learners’ proficiency in the use of these English prepositions. However, learners were incompetent in a class where the teachers used the narrative method as no questions were answered at the end of the lesson. It can be concluded that the question-and-answer method is appropriate for teaching the English prepositions of movement to Grade Six learners in this regard.